The Rhetoric of Origin: American National Ethos in Barack Obama's Dreams from My Father - Bhusal, Mahendra (SCHOLARS: Journal of Arts & Humanities, 2024)
This paper examines how Barack Obama ruminates on trials and tribulations from his past and ponders over his root in terms of biracial identity to explore his American ethos in his first memoir Dreams from My Father (1995). The paper argues that Obama struggles hard to locate his ethos out of the complexities of the relationships that his parents underwent in terms of their mixed marriages. Eventually he settles to his American identity, which is essentially biracial. From the perspective of Kenneth Burke's notion of 'identification', Obama evokes an awareness of American national ethos identifying with the American character as such and with this he explores his sense of purpose in life to be a public figure. He asserts that one of the fundamental characters of American national ethos is the biracial or multiracial that emanates from the contemporary American mixed society.